Trajectories of technogenic tritium in the Rhône River (France). (November 2020) - Morereau, A.; Lepage, H.; Claval, D.; Cossonnet, C.; Ambrosi, J.P.; Mourier, B.; Winiarski, T.; Copard, Y.; Eyrolle, F.
Abstract: Tritium is a radioisotope of hydrogen with a half-life of 12.32 years and was used for its luminescent properties by the watchmaking industry from 1962 to the 2008. Tritiated luminescent salts were integrated in the paints applied on the index and dial of watches and clocks. French and Swiss watchmaking workshops used more than 28 000 TBq of tritium over this period of time and produced almost 350 million watches. Despite the end of tritiated salts use in watchmaking workshops in 1992 in France and 2008 in Switzerland, high level of organically bound tritium (OBT) are still observed in sediments of the Rhône River downstream the Lake Geneva. Contamination of the Rhône River by tritiated hot particles since 1962 up to nowadays remains poorly documented. In order to assess the long term behavior and fate of technogenic tritium in this river and its trajectories in the river system, two sediment cores were collected at the upstream (UC) and downstream (DC) part of the Rhône River in France and OBT contents were determined. For both sedimentary cores, maximum OBT contents were registered over the 1980s when tritium was intensively used by watchmaking industries. These residual OBT contents are 1 000 to 10 000 fold higher than current natural background levels in riverine sediments. The OBT contents progressively decreased since 1989 with close effective half-life in upstream and downstream area (5 ± 2 years). The OBT contents were lower in DC than in UC due to the dilution by uncontaminated sediments delivered by tributaries not affected by the watchmaking industries. Trajectories analysis indicates that the resiliency of the Rhône River system in regards to this contamination would be reached in 14–70 years and in 14–28 years respectively for the upstream and downstream part of the river. Highlights: History of tritium used in French and Swiss watchmaking workshops was reviewed. OBT was analyzed in sediment cores collected upstream and downstream the Rhône River. Reconstructed time series testimony anthropic pressures over three major periods of time. Maximum OBT contents were registered over the 1980 with higher levels upstream. Current background level would be reached in 14–70 years.